Modes and moods of “Slave Anastácia,” Afro-Brazilian saint - Paul Christopher Johnson (Journal de la Société des Américanistes)
Agency activated through exchanges with saints is not simply present or absent. Rather it is emergent, depending on the mode of saints’ material and social configurations, and the mood evoked by a specific saint’s manifestation. In this essay I consider the history of an Afro-Brazilian saint called Slave Anastácia, as she signifies with varying social effects for different groups of ethno-racial users. I consider how saints become manifest in a given mode, and educe a particular mood. Mood is inseparable from intangible entities’ “presence.” In this essay, I leverage such radical disjunctures between the forms of presence generated by the same saint—Anastácia as suffering martyr, as serene helpmeet, as erotic object—to reconsider how saints work at the intersection of mode and mood. By paying attention to saints and mood, I seek to worry over-familiar terms like will and agency. Thinking through mood points us toward material conjunctures and emotional resonances whose agency is diffuse but nevertheless generates predispositions to act in certain ways.